2020
DOI: 10.1099/ijsem.0.004177
|View full text |Cite
|
Sign up to set email alerts
|

Leekyejoonella antrihumi gen. nov., sp. nov., a new member of the family Dermacoccaceae isolated from a cave soil

Abstract: A novel Gram-stain-positive, actinobacterial strain, designated C5-26T, was isolated from soil from a natural cave in Jeju, Republic of Korea, and its taxonomic position was investigated using a polyphasic approach. The organism was aerobic, and cells were non-spore-forming, non-motile cocci that occurred singly, in pairs, in triplets, in tetrads, in short chains or in irregular clusters. Colonies of the cells were circular, convex, entire and white. The peptidoglycan type was A4α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Caves represent an interesting environment that is unique and distinct from other terrestrial habitats. During a screening for novel actinobacteria from a natural cave in Jeju Island, Republic of Korea, many novel bacterial strains that were affiliated to the class Actinobacteria were described [9,[11][12][13][14][15]. Among them, it was found that two actinobacterial strains, designated as D2-41 T and D3-21, showed an uncertain taxonomic rank within the order Mycobacteriales through preliminary 16S rRNA gene sequence analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Caves represent an interesting environment that is unique and distinct from other terrestrial habitats. During a screening for novel actinobacteria from a natural cave in Jeju Island, Republic of Korea, many novel bacterial strains that were affiliated to the class Actinobacteria were described [9,[11][12][13][14][15]. Among them, it was found that two actinobacterial strains, designated as D2-41 T and D3-21, showed an uncertain taxonomic rank within the order Mycobacteriales through preliminary 16S rRNA gene sequence analysis.…”
Section: Introductionmentioning
confidence: 99%